A techno-economic study on the utilisation of airborne wind energy for reverse osmosis seawater desalination - Mahdi Ebrahimi Salari; Milad Zabihi; Jimmy Murphy (Heliyon)
Airborne wind energy is an emerging technology that can harness stronger and more consistent winds in higher altitudes using less mechanical and civil infrastructures than conventional wind energy systems. This article outlines a techno-economic study on using this technology for reverse osmosis seawater desalination in which a semi-permeable membrane process is used to remove salts and contaminants from water. To understand the techno-economic feasibility of such a system, this research work studies a 2 MW airborne wind-driven reverse osmosis plant. Different energy recovery devices are also studied to find their impact on improving the desalination plant's techno-economic performance. Results show the techno-economic practicality of an airborne wind-driven reverse osmosis plant with a competitive levelised-cost-of-water compared to similar-sized wind and solar energy-driven seawater desalination systems.